2019
DOI: 10.2174/1568026619666190712204050
|View full text |Cite
|
Sign up to set email alerts
|

Recent Progress in the Development of HIV-1 Entry Inhibitors: From Small Molecules to Potent Anti-HIV Agents

Abstract: Viral entry, the first process in the reproduction of viruses, primarily involves attachment of the viral envelope proteins to membranes of the host cell. The crucial components that play an important role in viral entry include viral surface glycoprotein gp120, viral transmembrane glycoprotein gp41, host cell glycoprotein (CD4), and host cell chemokine receptors (CCR5 and CXCR4). Inhibition of the multiple molecular interactions of these components can restrain viruses, such as HIV-1, from fusion with the hos… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
2
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(2 citation statements)
references
References 169 publications
0
2
0
Order By: Relevance
“…The receptor‐binding domain (RBD) of the spike protein (S) interacts with the protease domain of the angiotensin‐converting enzyme 2 (ACE2). Interference with the interactions between these proteins might provide a path to the development of antivirals that would prevent cell fusion and entry, as has been shown in the case of HIV through the development of peptidic and small‐molecule fusion inhibitors [36]. For that reason, accurate description of the interaction between the RBD and ACE2 is very important.…”
Section: Resultsmentioning
confidence: 99%
“…The receptor‐binding domain (RBD) of the spike protein (S) interacts with the protease domain of the angiotensin‐converting enzyme 2 (ACE2). Interference with the interactions between these proteins might provide a path to the development of antivirals that would prevent cell fusion and entry, as has been shown in the case of HIV through the development of peptidic and small‐molecule fusion inhibitors [36]. For that reason, accurate description of the interaction between the RBD and ACE2 is very important.…”
Section: Resultsmentioning
confidence: 99%
“…CD4-mimetic compounds (CD4mc) can potentially contribute to the control of the HIV-1 pandemic. Work from our group and others demonstrated that compounds that mimic the T-cell receptor CD4 and its interaction with the HIV-1 viral envelope glycoprotein trimer (Env) are able to inhibit viral entry into host cells by competitive inhibition and by premature allosteric activation of the HIV Env. Such premature activation leads to a series of conformational changes in Env that result in deactivation of the virus .…”
mentioning
confidence: 99%